2018
DOI: 10.1007/s11060-018-2914-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment neutrophil-to-lymphocyte ratio predicts for overall survival in brain metastases treated with stereotactic radiosurgery

Abstract: Introduction Neutrophil-to-lymphocyte ratio (NLR) is a surrogate for systemic inflammatory response and its elevation has been shown to be a poor prognostic factor in various malignancies. Stereotactic radiosurgery (SRS) can induce a leukocytepredominant inflammatory response. This study investigates the prognostic impact of post-SRS NLR in patients with brain métastasés (BM). Methods BM patients treated with SRS from 2003 to 2015 were retrospectively identified. NLR was calculated from the most recent full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 35 publications
5
35
1
Order By: Relevance
“…Indeed, all parameters with significant discrimination capacity were collected after the start of RT, rather than at baseline. In line with our results, a number of recently published studies suggest that post-treatment PBC parameters are associated with outcomes of cancer patients after RT or immunotherapy [29][30][31][32][33][34][35]. Barbetta shows that integrating multiple PBC parameters could predict the survival of patients with adult Tlymphoblastic lymphoma [38].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, all parameters with significant discrimination capacity were collected after the start of RT, rather than at baseline. In line with our results, a number of recently published studies suggest that post-treatment PBC parameters are associated with outcomes of cancer patients after RT or immunotherapy [29][30][31][32][33][34][35]. Barbetta shows that integrating multiple PBC parameters could predict the survival of patients with adult Tlymphoblastic lymphoma [38].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, all parameters with significant discrimination capacity were collected after the start of RT, rather than at baseline. In line with our results, a number of recently published studies suggest that post-treatment PBC parameters are associated with outcomes of cancer patients after RT or immunotherapy [3,9,21,25,27,32,40]. Barbetta A et al show that changes of NLR after CRT are associated with risk of recurrence in patients with oesophageal squamous cell carcinoma [3].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies involving HNSCC have shown an association between inflammation and worse prognosis [ 21 27 ]. However, information about the possible value of pretreatment NLR or PLR on toxicity is limited [ 18 29 ].…”
Section: Introductionmentioning
confidence: 99%